Testing The Physicochemical Properties Of Liquid Organic Fertilizer Waste Of Spincord Fish (Channa Striata) - Prastari, Cindytia; Ibrahim, Roy; Alhaviz, Alhaviz (JURAGAN - Jurnal Agroteknologi, 2024)
Fish wealth in the Indonesian region is abundant and efforts are continuously being made to increase the catch. Abundant fish catches become leftover fish or discarded fish due to various reasons, for example the fishermen's limited knowledge and facilities in fish processing methods. It turns out that the remaining fish or discarded fish can still be used. Nowadays snakehead fish (Channa striata) is widely used to make fish sauce, but in the manufacturing process only the flesh is used, this causes the skin and bones to become unusable waste. In general, fish waste contains many nutrients, namely N (Nitrogen), P (Phosphorus) and K (Potassium), which are components of organic fertilizer.The increase in waste production greatly influences global warming which triggers climate change. With proper processing in accordance with the environment and its presence in the environment, it is hoped that the environment will be clean, healthy and comfortable, in addition, appropriate waste can produce use value that will add income. From the research results, it can be concluded that the addition of the bromelain enzyme with a concentration of 150 mL produces the highest nitrogen content, namely 0.39%, while for the phosphorus content, the addition of 150 mL of enzyme shows a higher value, namely 0.168% and the highest nitrogen content, namely 0.037%, is owned by POC with the addition of 150 mL of bromelain enzyme.